GPS/BDS relative positioning assessment by zero baseline observation - Tang, Xu; Roberts, Gethin Wyn; Hancock, Craig Matthew; Yu, Jianjun (Elsevier, 2018)
A lot of researches proved integration of GPS and BDS could improve the position precision, since the Chinese BDS was opened to the Asia-Pacific users. Does this improvement come from better geometry by combining GPS/BDS or more precise measurement applied? The studies which have been focused on could be summarized in: how the integration system improved the reality ambiguity resolution; the advantage of integration by enhance the number of tracked satellites during high cut-off elevation, etc. In this paper, zero baseline observation was employed to assess the GPS/BDS standalone and integration system positioning precision without the effection of multipath, ionospheric and tropospheric delays, etc. DOP was used a lot to assess the geometry of GNSS satellites from previous research. GNSS positioning precision is not only determined by the precision of measurement, but also satellites geometry. This study presents the position error amplify indicator and variance amplify indicator to assess the geometry and carrier phase measurement contributions for the position precision improvement in GPS/BDS standalone and integration system applications. Additionally, difference level of random noise was simulated based on the real carrier phase measurements. North, east and up component of GPS/BDS standalone and integration systems’ position precision reduced by the increased noise of simulated measurement, but have different characteristic.